A 2000 patient retrospective assessment of a new strategy for burn wound management in view of infection prevention and treatment. Issue 3 (15th December 2017) - Glik, Justyna; Łabuś, Wojciech; Kitala, Diana; Mikuś‐Zagórska, Karolina; Roberts, Christopher D; Nowak, Mariusz; Kasperczyk, Aleksandra; Kawecki, Marek
Abstract : Infections in burn patients are still the principal cause of complications in burn injuries. The aim of this study is to assess a new strategy for burn wound management in view of infection prevention and treatment in the experience of the Burn Treatment Center in Siemianowice Śląskie. The applied methodology involved the analysis of patient records describing the hospital's epidemiological situation between 2014 and 2016. The analysis also included the use and cost of antibiotics, silver‐containing dressings, and other antiseptics relative to the number of sepsis cases, including those caused by Pseudomonas aeruginosa, as well as the mortality ratio. The total costs of prevention and treatment of infections were reduced, while the use of silver‐containing dressings and antiseptics increased. The number of patients with sepsis decreased, including cases caused by P. aeruginosa, and the mortality ratio was reduced. Introducing a strategy for burn wound‐oriented infection prevention and treatment in burn patients provides a number of benefits. It is also cost‐effective. Using locally applied active dressings and antiseptics can be a welcome choice for often‐unnecessary antibiotic therapy of a suspected or existing burn wound infection.